Prediction Of Future Temperature And Rainfall Characteristics Using Statistical Downscaling Model (Sdsm) For Ibu Bekalan Jelai Station In Kurau River Basin - khalil, arif; Arish, Nuraini (Progress in Engineering Application and Technology, 2021)
Events of environmental change and its effects on the water cycle have emerged in the last decades. Temperature and frequent variability as well as rainfall and flow patterns are rising, due to the impacts of climate change. Bukit Merah is the centre of tourism (Bukit Merah Laketown Resort) and farming (paddy irrigation). Nevertheless, climate change affects this region as it is affected by low dry seasonal water levels and high quantities of monsoon water causing floods. This work discusses the use of statistical downscaling model (SDSM) in the Bukit Merah reservoir to forecast the expected rainfall and climate changes. The SDSM was optimized and developed for future possible scenarios climate factors such as temperature and precipitation use GCMs (global climate models). The study forecast estimated 10 years (2020-2030) of rainfall and temperature at the Bukit Merah reservoir.